Genetic regulation of major immunogenic protein accumulation in peanut seeds - Tariq Alam; Gautam Saripalli; Carolina Ballen-Taborda; Sachin Rustgi (Functional & Integrative Genomics, 2026)
Peanut is a major oilseed crop in the U.S., which ranks third globally in production, with South Carolina ranking sixth nationally. Despite their economic and nutritional value, peanuts are unsuitable for 1–2% of the U.S. population due to allergic reaction, including anaphylaxis, making the development of reduced-allergen peanuts a priority. This study aimed to identify peanut lines with reduced Ara h1, h2, h3, and h6 levels and to elucidate their genetic regulation using genome-wide association studies (GWAS). Ninety-two accessions from the U.S. peanut mini-core collection were screened using ELISA and SDS-PAGE, and the resulting data were evaluated for association with 5,532 SNP markers. Substantial phenotypic diversity was observed. Twenty-three lines with extreme protein phenotypes were further evaluated by RP-UPLC, and nine by LC-MS. GWAS identified 165 marker-trait associations (MTAs) across raw and log-transformed datasets, with 13 MTAs common to both analyses. These MTAs were grouped into protein quantitative loci (PQLs), revealing six trans -PQLs and cis -PQLs for two of the five Ara h genes. Seed-expressed candidate transcription factors (TFs), including MYB, MYC, ERF, and bZIP, and pleiotropic PQLs were identified. Promoter analysis (1 kb upstream of transcription start site or TSS) of the corresponding Ara h genes revealed binding sites for TFs underlying these PQLs. We hypothesize that these TFs trans-regulate the Ara h genes either directly or through a regulatory cascade. These findings provide initial insights into the regulatory landscape of Ara h genes and will facilitate breeding for reduced allergen content in peanut.

Plant cytogenetics blurring disciplinary boundaries to sustain global food security - Sachin Rustgi (The Nucleus, 2023)

An insight into the gene-networks playing a crucial role in the cotton plant architecture regulation - Salman Naveed; Michael Jones; Todd Campbell; Sachin Rustgi (The Nucleus, 2023)

Heat tolerance as a function of membrane lipid remodeling in the major US oilseed crops (soybean and peanut) - Sachin Rustgi; Jyoti Prasad Kakati; Zachary T. Jones; Zolian S. Zoong Lwe; Sruthi Narayanan (Journal of Plant Biochemistry and Biotechnology, 2021)

Probing early wheat grain development via transcriptomic and proteomic approaches - Mingming Yang; Yang Liu; Jian Dong; Wanchun Zhao; Samneet Kashyap; Xiang Gao; Sachin Rustgi; Shanshan Wen (Functional & Integrative Genomics, 2020)

Development of wheat genotypes expressing a glutamine-specific endoprotease from barley and a prolyl endopeptidase from Flavobacterium meningosepticum or Pyrococcus furiosus as a potential remedy to celiac disease - Claudia E. Osorio; Nuan Wen; Jaime H. Mejias; Bao Liu; Stephen Reinbothe; Diter von Wettstein; Sachin Rustgi (Functional & Integrative Genomics, 2019)

NADPH:protochlorophyllide oxidoreductase B (PORB) action in Arabidopsis thaliana revisited through transgenic expression of engineered barley PORB mutant proteins - Frank Buhr; Abderrahim Lahroussi; Armin Springer; Sachin Rustgi; Diter von Wettstein; Christiane Reinbothe; Steffen Reinbothe (Plant Molecular Biology, 2017)

DNA Methylation Changes Induced in Rice by Exposure to High Concentrations of the Nitric Oxide Modulator, Sodium Nitroprusside - Xiufang Ou; Tingting Zhuang; Wenchao Yin; Yiling Miao; Bo Wang; Yunhong Zhang; Xiuyun Lin; Chunming Xu; Diter von Wettstein; Sachin Rustgi; Bao Liu (Plant Molecular Biology Reporter, 2015)

Virus-induced gene silencing (VIGS) of genes expressed in root, leaf, and meiotic tissues of wheat - Harvinder S. Bennypaul; Jasdeep S. Mutti; Sachin Rustgi; Neeraj Kumar; Patricia A. Okubara; Kulvinder S. Gill (Functional & Integrative Genomics, 2012)

A preliminary genetic analysis of fibre traits and the use of new genomic SSRs for genetic diversity in jute - Reyazul R. Mir; Sachin Rustgi; Shailendra Sharma; Ravinder Singh; Aakash Goyal; Jitendra Kumar; Anupama Gaur; Akhilesh K. Tyagi; Haseena Khan; Mohit K. Sinha; Harindra S. Balyan; Pushpendra Kumar Gupta (Euphytica, 2008)

Linkage disequilibrium and association studies in higher plants: Present status and future prospects - Pushpendra K. Gupta; Sachin Rustgi; Pawan L. Kulwal (Plant Molecular Biology, 2005)